Evaluating the genetic architecture of the Japanese Wagyu breed within the United States - Heffernan, Kathryn, author; Speidel, Scott E., advisor; Thomas, Milt, committee member; Enns, Mark, committee member; Blackburn, Harvey, committee member; Holt, Timothy, committee member (Colorado State University. Libraries, 2022)
The objective of this thesis is to better understand the genetic architecture of Japanese Wagyu cattle in the United States to improve on current breeding strategies, as well as help to develop new strategies to increase the genetic diversity of the U.S. Wagyu population. For this study, pedigree data (n = 48) were collected on full-blood Japanese Wagyu sires and dams, and high-density genotype data (n = 414) were collected on Japanese Wagyu, Ayrshire, Brahman, Brangus, Devon, Holstein, Milking Devon, Milking Shorthorn, Shorthorn, Simmental, South Devon, Angus, Jersey Island, and Brown Swiss cattle. Inbreeding coefficients were calculated from the pedigree data and averaged 0.19, with a minimum coefficient of zero, max coefficient of 0.43, and a standard deviation of 0.08. Using the genotypes, a principal component analysis (PCA), an admixture graph, and a phylogenetic tree were computed to ascertain the population structure and breed composition of modern Japanese Wagyu cattle in relation to other breeds. The majority of the Japanese Wagyu had an elongated dispersal that overlapped with the origin of the PCA graph. Japanese Wagyu also averaged 85.5% indicine influence as indicated by the admixture graph, and the phylogenetic tree showed Japanese Wagyu as the closest branch to the root breed Brahman. These results suggest that Japanese Wagyu are an inbred population. While mostly Bos indicus, these results suggest that Japanese Wagyu are admixed with low percentages of Bos taurus breeds such as Simmental and Brown Swiss.
Keywords: Japanese Wagyu; inbreeding; population genetics